PD-L1 status does not predict the outcome of BRAF inhibitor therapy in metastatic melanoma - Schaper-Gerhardt, Katrin; Utikal, Jochen (European journal of cancer, 2018)
AbstractBackground:Targeted therapies with BRAF plus MEK inhibitors (BRAFi; MEKi)represent the major treatment strategy for patients with BRAF-mutated metastatic melanoma(MM). Previous analyses suggested a correlation between programmed death-ligand 1 (PD-L1)expression in tumour tissues and the outcome of targeted therapies. This study investigatedPD-L1 as a potential predictive biomarker of BRAFi-based targeted therapies in MM patients
Gesehen am 28.05.2019
Available online 28 November 2017